Uganda’s rangeland policy: intentions, consequences and opportunities - Byakagaba, Patrick; Egeru, Anthony; Barasa, Bernard; Briske, David D. (Pastoralism, 2018)
This paper analyses Uganda’s rangeland policies and their ecological and socio-economic consequences, beginning in pre-colonial times. The paper interrogates what informed these policies, their objectives and outcomes that have been realized. Policy actions are recommended to correct the deficiencies identified in the analysis. This analysis shows that policies were based on western European resource management, classical rangeland ecological and economic theory and marginalization narratives, rather than the socio-ecological realities of Uganda’s rangelands. The unique attributes of Uganda’s rangelands were largely unrecognized. Consequently, pastoralists, dependent on the rangeland resources and ecosystem services, were displaced and exposed to incremental risks, poverty and a breakdown of social networks and safety nets as well as decline in rangeland productivity. In the rangelands of north-eastern Uganda for example, the inflexibility and immobility and forms of exploitation dictated to the Karimojong pastoralists led to increased soil erosion and decline in land productivity. Similarly, with increased parcelization, individualization and sedentarization in central and south-western Uganda, pastoral communities became impoverished as rangeland resources became increasingly limited. This increased their exposure to the vagaries of extreme events such as droughts, floods and disease outbreaks, thereby increasing livestock mortality and recurrent food insecurity. Expansion of competing land uses has reduced the net availability of rangeland resources, often with the support of external incentives. Current policies promoting fire exclusion have led to increased bush encroachment, while other policies have undermined the centrality of commons’ governance practices and institutions. Uganda’s land use policies ought to emphasize a more balanced socio-ecological perspective (ensuring net gain especially in the interaction of resource use between humans and the environment) that supports the functionality and productivity of rangeland ecosystems and their ability to deliver socioeconomically important ecosystem services and address human needs. This can be through promotion of common property and consolidation of land for optimal utilization of ecological heterogeneity and enhancement of resilience. Mapping of transhumance corridors to determine ways through which mobility can increase herds’ access to forage and water between and within years will be equally important to enhance pastoralists’ resilience. Policy actions that provide payments for conservation stewardship of rangelands should be considered to incentivize land owners to maintain their land as rangelands. Assessment is required of the ecological and social impacts of fire, in order to determine optimal fire regimes and amendment of laws that ban the use of fires, so as to promote prescribed burning in rangelands. Achieving all these will require reforms that clearly delineate policy and legal frameworks for sustainable rangeland use and management.
Keywords: Colonial; Disruption; Encroachment; Pastoralists; Regulations; Uganda